Enhanced CO2 sorption performance of CaO/Ca3Al2O6 sorbents and its sintering-resistance mechanism. (1st August 2017) - Jing, Jie-ying; Li, Ting-yu; Zhang, Xue-wei; Wang, Shi-dong; Feng, Jie; Turmel, William A.; Li, Wen-ying
Graphical abstract: Highlights: Sorbent with CaO/Al2 O3 mass ratio of 8:2 obtained the best cyclic sorption performance. Ca3 Al2 O6 reduced CO2 diffusion resistance and gave sorbents high absorptivity. The cyclic sorption stability is due to the small original surface free energy. Abstract: CaO-based CO2 sorbents play a significant role in sorption enhanced methane steam reforming process for hydrogen production and CO2 emission reduction. However, the sorbents suffer from decreasing CO2 sorption capacity and stability due to the sintering of CaO grains. In this study, we modified CaO sorbents by incorporating Al to obtain CaO/Ca3 Al2 O6 sorbents via a modified sol-gel method. CO2 sorption evaluation shows that the relative quantity of CaO to Al2 O3 plays an overwhelming role in the CO2 sorption capacity and stability of the CaO/Ca3 Al2 O6 sorbents. Superior CO2 sorption ratio (51.92% for sorbent C8A2 at 500 °C) is achieved, which is 5 times higher than that of the as-synthesized pure CaO sorbent. The high CO2 sorption ratio is due to the existence of inert Ca3 Al2 O6, which decreases the diffusion resistance of CO2 through product layer during the carbonation reaction. Meanwhile, the superior CO2 cyclic sorption stability is ascribed to the small original surface free energy of the as-synthesized sorbents.